Demonstrating the feasibility of collecting secondary, de‐identified data on Australian patients receiving treatment as part of a Medicine Access Programme. Issue 1 (14th January 2020) - Lok, Sheau W.; De Boer, Richard; Cordwell, Cassandra; Marx, Gavin; Fox, Peter; Hasovits, Csilla; Rutovitz, Joseph; Harold, Michael; Tran, Ben; Wong, Hui‐Li; Gibbs, Peter
Abstract: Background: In Australia, data generated from the carefully selected, treated and monitored patients enrolled in clinical trials largely inform routine care and funding approvals. Medicine Access Programmes (MAP) enable drug access and while potentially a rich source of data, historically have not collected data beyond a participant list. Aims: To explore the feasibility of using MAP to identify patient populations for inclusion in non‐interventional studies. Methods: Clinicians affiliated with the Walter and Eliza Hall Institute engaged with Roche to implement PeRSIA, a secondary data use non‐interventional study of patients receiving neoadjuvant pertuzumab for non‐metastatic HER2+ breast cancer. The study utilised a pre‐existing Roche‐sponsored MAP to identify clinicians as data contributors. Data security, ownership and reporting issues were addressed utilising the BioGrid platform and standards developed for existing Walter and Eliza Hall Institute registries. Disease experts developed project‐specific Case Report Forms documenting treatment, surgical and cancer‐specific outcomes, and adverse events. Results: To date, 12 of 16 (75%) clinicians approached to participate in PeRSIA are contributing de‐identified data. From February through September 2018, data on 41 patients from seven centres were collected. Median patient age is 56 years (range 36–81), 36 (88%) had Stage 2 to 3 disease and 27 (66%) were node positive. The median number of cycles of neoadjuvant pertuzumab planned was 4. Conclusions: This initial report is, to our knowledge, the first description of a secondary data use non‐interventional study collecting comprehensive data on patients enrolled, independently, in a MAP. This effort continues and opportunities with other industry partners are being pursued.